HUBUNGAN PENGETAHUAN DAN SIKAP TERHADAP KEBIASAAN MEROKOK SISWA SMP NEGERI 1 DELI TUA TAHUN 2025 - Anggi Nafina Siagian; Lelly Anggralisti; Sindy Arabina Karo Sekali; Ita Nasari Zega; Ribka Marinto Sitorus (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Background: Smoking during adolescence remains a major public health issue in Indonesia. Adolescence is a period of identity exploration and vulnerability to environmental influences. Adolescents’ knowledge and attitudes toward smoking play a crucial role in shaping their smoking habits. This study aims to determine the relationship between knowledge and attitudes and smoking habits among students at SMP Negeri 1 Deli Tua in 2025. Methods: This research employed an analytical design with a cross-sectional approach. The sample consisted of 30 students selected using total sampling. The research instrument was a closed-ended questionnaire measuring knowledge, attitude, and smoking habits. Data were analyzed using univariate and bivariate methods with the Chi-Square test at a 5% significance level. Results: The analysis showed a significant relationship between knowledge and smoking habits (p = 0.012), and between attitude and smoking habits (p = 0.004). Students with low knowledge and negative attitudes were more likely to have smoking habits. Conclusion: There is a significant relationship between knowledge and attitudes and students' smoking habits. Educational interventions and attitude development need to be strengthened to prevent smoking behavior during adolescence.